2017
DOI: 10.4102/sajid.v32i4.37
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sepsis in a Nigerian Tertiary Hospital: Clinical features, clinical outcome, aetiology and antibiotic susceptibility pattern

Abstract: Background:Neonatal sepsis is a significant cause of neonatal mortality in developing countries. The aetiological agents and their antimicrobial susceptibility patterns are dynamic.Objectives: This study determined clinical features, aetiology, antimicrobial susceptibility and clinical outcome of neonatal sepsis in a Nigerian Tertiary Hospital.Methods: Neonates undergoing sepsis evaluation at a Nigerian Tertiary Hospital were included in the study. Demographic and clinical information were obtained using stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 6 publications
(10 reference statements)
8
22
2
Order By: Relevance
“…63 Hospital-based studies were mostly tertiary referral facilities (university or large national hospitals), and only 23 from district or secondary referral hospitals. 34,48,51,54,[59][60][61][62][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] 139 studies were in urban settings whereas others reported data from predominantly rural populations: five studies from Kenya, 54,61,64,65,68 three from Mozambique, 59,72,73 two from Nigeria, 79,80 and one from Cameroon. 77 88 studies involved prospective data collection, 61 were retrospective reviews (26 laboratory-based surveillance of aetiological data), and two studies had both retrospective and prospective components.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…63 Hospital-based studies were mostly tertiary referral facilities (university or large national hospitals), and only 23 from district or secondary referral hospitals. 34,48,51,54,[59][60][61][62][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] 139 studies were in urban settings whereas others reported data from predominantly rural populations: five studies from Kenya, 54,61,64,65,68 three from Mozambique, 59,72,73 two from Nigeria, 79,80 and one from Cameroon. 77 88 studies involved prospective data collection, 61 were retrospective reviews (26 laboratory-based surveillance of aetiological data), and two studies had both retrospective and prospective components.…”
Section: Resultsmentioning
confidence: 99%
“…Case ascertainment by physician diagnosis was reported in 44 (54%) of 81 observational studies, 26 of which documented the individual clinical signs used for the diagnosis of neonatal sepsis or meningitis. Only seven studies 36,63,74,[86][87][88][89] reported using the WHO/IMCI clinical algorithm, two studies 90,91 used the French National Agency for Accreditation and Health clinical diagnostic criteria, 92 and one Ugandan study 93 reported using criteria adopted from International Paediatric Sepsis Consensus 94 and Indian Academy of Paediatrics. 95 30 (37%) of these observational studies reported microbiological or laboratory criteria for diagnosis of neonatal infection syndromes (sepsis or meningitis), and 56 studies (69%) described micro biological sample type and sampling strategy (clinical indication vs routine sampling) as well as number of neonates sampled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from four other countries, including Thailand, found an incidence of 5 per 1000 live births [17]. The prevalence was 21.8 or more in Nigeria [12,13]. A report from the largest hospital in Indonesia found an incidence of 35% [44].…”
Section: Discussionmentioning
confidence: 98%
“…The exact data of neonatal sepsis in the LMIC is limited [8][9][10][11]. Two studies from Nigeria showed a prevalence rate of 47.2 and 21.8% [12,13]. A study from Indonesia found 46.6% prevalence [14].…”
Section: Introductionmentioning
confidence: 99%